Advances in transportation geotechnics II : proceedings of the 2nd International Conference on Transportation Geotechnics (2nd ICTG), Hokkaido, Japan, 10-12 September 2012 /: proceedings of the 2nd International Conference on Transportation Geotechnics (2nd ICTG), Hokkaido, Japan, 10-12 September 2012. (©2012) - Unknown
No abstract available